Cardiac specific knock-down of peroxisome proliferator activated receptor α prevents fasting-induced cardiac lipid accumulation and reduces perilipin 2. - Natasha Fillmore; Natasha Fillmore; Vincent Hou; Junhui Sun; Danielle Springer; Elizabeth Murphy (PLoS ONE, 2022)
While fatty acid metabolism is altered under physiological conditions, alterations can also be maladaptive in diseases such as diabetes and heart failure. Peroxisome Proliferator Activated Receptor α (PPARα) is a transcription factor that regulates fat metabolism but its role in regulating lipid storage in the heart is unclear. The aim of this study is to improve our understanding of how cardiac PPARα regulates cardiac health and lipid accumulation. To study the role of cardiac PPARα, tamoxifen inducible cardiac-specific PPARα knockout mouse (cPPAR-/-) were treated for 5 days with tamoxifen and then studied after 1-2 months. Under baseline conditions, cPPAR-/- mice appear healthy with normal body weight and mortality is not altered. Importantly, cardiac hypertrophy or reduced cardiac function was also not observed at baseline. Mice were fasted to elevate circulating fatty acids and induce cardiac lipid accumulation. After fasting, cPPAR-/- mice had dramatically lower cardiac triglyceride levels than control mice. Interestingly, cPPAR-/- hearts also had reduced Plin2, a key protein involved in lipid accumulation and lipid droplet regulation, which may contribute to the reduction in cardiac lipid accumulation. Overall, this suggests that a decline in cardiac PPARα may blunt cardiac lipid accumulation by decreasing Plin2 and that independent of differences in systemic metabolism a decline in cardiac PPARα does not seem to drive pathological changes in the heart.